Integrability of the Basener–Ross model with time-dependent coefficients - F., Güngör; P. J., Torres (Springer Science and Business Media LLC, 2019)
The Basener-Ross system is a known model in Population Dynamics for the interaction of consumers and resources in an isolated habitat. For an extended version with time-dependent coefficients as a model of possible variations of the environtmental conditions, some relations among the coefficients are provided leading to the integrability of the system.

10 pages, 1 figure
Keywords: exact solution; integrability; A05, 34c14, 92d25; Lie symmetry; Population dynamics (general); Mathematics - Classical Analysis and ODEs; Qualitative investigation and simulation of ordinary differential equation models; Explicit solutions, first integrals of ordinary differential equations; Classical Analysis and ODEs (math.CA); FOS: Mathematics; predator-prey; Symmetries, invariants of ordinary differential equations; Basener-Ross model